Holistic Assessment of Urban Transportation Electrification Strategies Considering Air Quality, Energy Efficiency, and Public Health Benefits - Farida Arfani; Sofiansyah Fadli; Saikin Saikin (International Forum of Researchers and Lecturers, 2024)
Urbanization has significantly impacted air quality in cities, with vehicular emissions being a major contributor to pollution. This study explores the potential benefits of electrifying urban transportation, specifically through the adoption of electric vehicles (EVs). The findings indicate that EVs substantially reduce key pollutants such as CO₂, NOx, and PM₂.₅, improving urban air quality and mitigating climate change. The analysis shows that EV adoption can lead to a 50% reduction in CO₂ emissions in high EV adoption scenarios (70% EVs). Additionally, EVs are more energy-efficient than conventional vehicles, consuming significantly less energy per kilometer. This transition not only reduces dependence on fossil fuels but also supports sustainable urban development. Furthermore, the study highlights the public health benefits of electrification, with reduced levels of harmful pollutants leading to lower incidences of respiratory and cardiovascular diseases. Public health surveys reveal strong support for EV adoption, with respondents believing it would significantly improve air quality and health outcomes. In conclusion, the electrification of urban transportation presents a multifaceted approach to environmental sustainability, energy efficiency, and public health improvement.